Kewarisan Masyarakat Muslim dalam Konteks Indonesia - Yuliatin Yuliatin (INNOVATIO: Journal for Religious Innovation Studies, 2016)
Indonesia is one country that has the largest population in the world. Religious diversity and customs inherent in community life, but does not mean it makes the pluralistic Indonesian society divided and fragmented. Precisely these differences condition they respect and value between one another. Despite the fact that the majority of Indonesian people are Muslims, but the application of the laws of force in it are not necessarily subject to the laws of Islam alone. In the matter of implementation of the division of the estate, Indonesia's Muslim population is very varied, either by using the Islamic inheritance law as well as the customary inheritance law. Islamic inheritance executed by referring to the rules contained in the Compilation of Islamic Law which is certainly a source of law of the KHI major source of al-Quran and al-Hadith that there must be collaboration mujtahids interpretation of a well-formulated for the benefit of Indonesian Muslims. While the implementation of the division of estate, by using the customary inheritance law can be seen in the pattern of distribution of inheritance; 1. mayor at men (indigenous Lampung), the eldest son has full authority to the inheritance of parents, the responsibility of parents turn when their parents died or switched while the oldest boy has been married, children, women do not have rights to inheritance by reason of girls have given a Sergeant at the time of marriage; 2. mayoral women (indigenous Semendo South Sumatra), where the full authority over the estate such as houses, fields, and gardens turn to the oldest daughter "waistband", it manages the estate and can be utilized by all the heirs, apart from such property can be divided according to Islamic inheritance law; 3. The individual (custom Seberang Kota Jambi), inheritance becomes full rights of each of the heirs, both male, and female. The division of the estate according to the agreement with the equal distribution principle or superiority of heirs